Kajian Lanskap Desa Lela Kabupaten Sikka, Nusa Tenggara Timur - Wilhelmus Bernadus Bisa; Irawan Setyabudi; Rizki Alfian (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2022)
Lela village has a population of mostly ethnic flores. Most of the inhabitants are farmers. The main agricultural products in this village are coffee, cocoa and others. Law 6 of 2014 concerning villages (UU Desa) states that villages are villages and traditional villages or what is called by another name, hereinafter referred to as village, is a legal community unit that has territorial boundaries that are authorized to regulate and manage government affairs, the interests of the local community based on community initiatives, origin rights, and/or traditional rights that are recognized and respected in the system of government of the unitary state of the republic of Indonesia. The village is an area that has great natural potential. from these natural resources, can be used as a source of food and raw materials. These natural resources owned by the village can be used as a driving force to increase national economic development. This is because Indonesia adheres to a people's economic system which is proven to be able to support the national economy even in times of crisis. However, the reality is that most villages in Indonesia are underdeveloped villages. The livelihood of the majority of the population in the village of Lela Sikka is farming. In accordance with the climate of the area, the majority of them are dry land farmers, the rest are fishermen, entrepreneurs and employees, both public and private. Sikka Regency is a regency located in the province of East Nusa Tenggara, Indonesia. The capital city of Sikka district is Maumere, FGD can simply be defined as a discussion that is carried out in a systematic and focused way about a particular issue or problem. (Bisjoe, A. R. H. 2018). “FGD is a systematic process of collecting data and information on a specific, very specific problem through group discussions”. In more detail, the definition of FGD was put forward by (Prihatin, E. 2014). Kata Kunci: Lela village, Historical Landscape Study, Historical Characteristics In Lela Village